Hubungan Status Gizi dengan Perkembangan Balita Umur 3 – 5 Tahun di PAUD Wilayah PUSKESMAS Kesugihan I Kabupaten Cilacap - Alis Mugiharti; Enik Sulistyoawati (JURNAL RISET GIZI, 2013)
Background : The first five years of life is a sensitive period of children. This period is also called ’the gold period’, ’the window of opportunity’, and ‘the critical period’. In less than five year period, the ability of speaking and language, creativity, social awareness, emotion and intelligence develop so fast. One of influencing factor is nutrition status. Objective :The purpose of the research is to find out the relationship between the nutrition statuses with the development of under-five children in pre- school education in the Puskesmas Kesugihan I Cilacap Districts. Method: This research is the explanative research with the cross sectional approach. The analyzed population is all the children in the age of 3 until five in pre-school education in the area of Puskesmas Kesugihan I Cilacap Districts. The sample of this research is 90 children. The technique of data collection is a interviewed with Development Pre Screning Quesioner. Fisher’s exact test analized was done to got relationship between variabels. Result: The percentage of over weight was 41 children (45.6%), well-nourished was 32 children (35.6%), and wasting was 17 children (18.9%). The development of dominant sample for amount 58 children (64.4%) is appropriate; the development of 27 children (30%) is doubtful and 5 children (5.6%) with development’s deviation. There is a relationship between the nutrition status with the development of children 3 -5 years old (p= 0,025). Conclusion: There is a meaningful relationship between the nutrition status with the development of children3 -5 years old (p= 0,025).